Enhancing Fishing Port Services Quality to Support Fish Supply Chains of the Island Fisheries at the Belitung Island - Farisha Safrina Nur; Suadi Suadi; Suwarman Suwarman (Universitas Gadjah Mada, 2023)
Fishing ports are crucial to the sustainable management of fisheries resources and enterprises that depend on the fishery. The objective of this study was to analyze the levels of facilities availability and service quality of fishing ports in the islands through a case study of Tanjungpandan Islands Fishing Port in Belitung Island. This study was conducted by combining survey methods, observation, as well as in-depth interviews with the port users and managers.Â Due to Covid-19 pandemic, field research was conducted in two periods: from September to October 2020 and from January to February 2022. Respondents were selected by applying the snowball sampling method and resulted in 70 selected respondents, consisting of fishermen, skippers, traders, factory managers or fish processing units, and port managers. Structured questionnaires were used for data collection.Â It proceeded into descriptive-qualitative analysis and combined with SERVQUAL and IPA (Importance Performance Analysis) methods. The study demonstrated that six port facilities failed to meet the Nusantara (inter-island) fishing port standards as outlined in the Minister of Marine Affairs and Fisheries' Regulation No. 8, year 2012. Eight port services that were considered important indicated low performance to support the islandâ€™s fish supply chain. The total score of basic, functional, and supporting facilities was 60.46% (within 0 â€“ 100% scale) and considered as relative â€œgoodâ€. Therefore, given that the port is the main hub of marine fisheries activities on Belitung island, it is crucial to increase the accessibility, quality, and services of fishing port facilities in order to support the fish supply chain in the islands.